Exploring Racism in the Freedom Writers (2007): Van Dijk's Critical Discourse Analysis of Social Context and Social Ignition Dimensions - Joko Wibowo (Universitas Al-Qolam Malang, 2025)
This research analyzed racism in Freedom Writers (2007) through Van Dijk’s Critical Discourse Analysis framework, exploring societal influences, racial conflicts, and resolution strategies. The research revealed The Freedom Writers portrayed systemic racism through classroom discrimination, gang conflicts, and inequality. Using Van Dijk’s CDA, highlighted education and empathy as tools for change, with activities like the Line Game fostering unity. Empowerment through storytelling and linking struggles to global issues, such as the Holocaust, emphasized collective efforts for lasting systemic reform and social transformation. Keywords: Racism, Freedom Writers (2007, Van Dijk’s Critical Discourse Analysis (CDA), Social Context, Social Ignition.